Advances in the diagnosis and treatment of cutaneous T-cell lymphoma - Hongzhong JIN; Keyun TANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Mycosis fungoides (MF) and Sezary syndrome (SS) are important representatives of the heterogeneous group of cutaneous T-cell lymphoma. The diagnosis of MF/SS is based on the clinical, histopathologic and immunohistochemical findings, flow cytometric analysis of peripheral blood and T-cell receptor gene rearrangement, as well as other genetic analysis. The treatments for MF/SS are always stage-oriented and are classified into topical (skin-directed) and systemic therapies. Chinese and international experts in this field have updated recommendations and guidelines for the diagnosis and treatment of MF/SS. There are tremendous evolvements in the diagnosis of MF/SS, including molecular diagnostic methods, molecular biomarkers, dermoscopic imaging and artificial intelligence. Novel disease-specific targeted therapy, biologic therapy and immunomodulatory drugs have emerged. This review summarizes advances in the diagnosis and treatments of MF/SS, which may provide a reference for clinical practice and future research.